Porter’s Five Force Model For Superiority Of Micro Small And Medium Enterprises (Sme’s) In Face The Asean Economic Communiy (Mea) - Julita UMSU; Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This study aims to provide input and an effective way for SMEs in order to have a competitive advantage, especially in the face of the MEA, it is necessary for the existence of a strategy to create competitive advantage in the era of MEA. Many strategies to create competitive advantage and one of them is Porter's Five Forces. This study uses research and development. Respondents in this study is small and medium businesses (SMEs) in the district of Deli Serdang. Data collection techniques using questionnaires and interviews / structured interviews and data analysis techniques using descriptive analysis techniques. The results showed that the model of five forces porter that include competition among similar companies, the threat of new entrants, the threat of substitute products, bargaining power of buyers and bargaining power of suppliers is still included in the category enough or moderate, it indicates the presence of obstacles or problems faced by SMEs in Regency Deli Serdang.Disamping five forces model of porter, the addition of the supporting indicators of the ability of innovation and technology as well as the government's attention is also included in the category enough or moderate, it indicates that the supporting indicators are still facing obstacles or problems.Keywords: Porter's Five Force, SMEs, MEA